Preventive Diagnosis of Biological Colonization and Salt-Related Decay on the Frescoes of the “Oratorio dell’Annunziata” (Riofreddo, Latium, Italy) to Improve Conservation Plans - Flavia Bartoli; Annalaura Casanova Municchia; Marco Tescari; Ilaria Ciccone; Paolo Rosati; Alessandro Lazzara; Maria Catrambone (Applied Sciences)
The frescoed Annunziata Oratory chapel in Riofreddo (Italy), a unique testimony to the pontificate of Martin V, sheds light on the trade routes of Ninfa in the first half of the 15th century. Despite having undergone several restorations in the past (the most recent in the 2010s), the Oratory presents serious conservation issues. At first glance, there are no evident signs of biological colonization; rather, the most obvious damage is attributed to detachments and saline efflorescence. Biological colonization at several points was identified using various diagnostic field and laboratory techniques such as ATPase point analysis, field stereoscopy in visible and UV light, culture-based and molecular approaches, Raman spectroscopy, and SEM analysis, biological colonization at several points was identified. The characterization of salt efflorescence was carried out using ion chromatography analysis. The presence of bacteria, fungi and algae, which are also linked to saline efflorescence, was observed. A clear correlation between the biological colonization and salt efflorescence composition was highlighted by our results, as well as the potential sources of microorganisms and salts via the capillary rise of groundwater. This early diagnostic approach regarding the presence of lithobionts and salt efflorescence demonstrates the complex interplay between environmental factors and microbial colonization, which can lead to biodeterioration processes.